1983
DOI: 10.1152/ajprenal.1983.244.2.f195
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic hormone-dependent membrane capacitance and water permeability in the toad urinary bladder

Abstract: Antidiuretic hormone (ADH) increased the electrical capacitance of apical membrane of the toad bladder; this effect was modulated by the osmotic gradient across the tissue. Capacitance was measured from the transepithelial voltage response to constant-current pulses using bladders depolarized with KCl-sucrose serosal solution to reduce basolateral resistance and with Na-free mucosal solution to increase apical membrane resistance. Addition of ADH (20 mU/ml) increased capacitance by 28 +/- 9% (mean +/- SD) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…We found that both ADH and long term aldosterone increased apical membrane ␤-xENaC. In both of these conditions, estimates of channel activity by electrophysi-ologic techniques or biochemical methods suggest an increase in the number of active apical membrane holochannels (20,21,67,68,73). This suggests that ␤-xENaC delivered from intracellular compartments may assemble with ␣␥ heterodimers already present at the cell surface.…”
Section: Figmentioning
confidence: 80%
“…We found that both ADH and long term aldosterone increased apical membrane ␤-xENaC. In both of these conditions, estimates of channel activity by electrophysi-ologic techniques or biochemical methods suggest an increase in the number of active apical membrane holochannels (20,21,67,68,73). This suggests that ␤-xENaC delivered from intracellular compartments may assemble with ␣␥ heterodimers already present at the cell surface.…”
Section: Figmentioning
confidence: 80%
“…In the case ofglucose transport, microfilament disruption with cytochalasin B resulted in impaired glucose transporter trafficking and diminished glucose uptake (50-53). Toad bladder studies have revealed that water transport is dependent upon water channel movement through the cytoskeleton, since water transport was inhibited after disruption of either microfilaments (54)(55)(56)(57) or microtubules (54,55,57). Although endocytosis through cytoskeletal domains appears to be required for a number of AP functions, there is little information about the role of the cytoskeleton in receptor-mediated signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…ADH stimulation without net osmotic water flow (no osmotic gradient) produces aggrephore fusion without apical membrane retrieval (9,10,26 (27 (Fig. 1B).…”
Section: Lactoperoxidase/glucose Oxidase Iodination Of the Apicalmentioning
confidence: 98%